DETERMINAN TINGKAT MIGRASI TENAGA KERJA KELUAR INDONESIA (Studi Kasus: Provinsi-Provinsi di Indonesia) - Alifia Anastasya (2021)
Migration in the era of globalization is a form of self-actualization in fulfilling aspects of life. The decision on international migration of workers who choose to work outside Indonesia does not just happen, there are various factors that influence this, including the driving factors related to economic differences and the uneven development of a region. This study is a quantitative study that aims to determine the influence of the Labor Force, Poverty, GRDP per capita and Education on Indonesian Labor Migration. This study uses data from 5 provinces in Indonesia including East Java, Central Java, West Java, Lampung and West Nusa Tenggara for the period from 2011 to 2020. The method chosen is the Fixed Effect Model (FEM). The results of this study indicate that (1) the labor force influences the migration of Indonesian workers, because as a developing country, Indonesia has a population that is dominated by productive age. The abundance of the workforce that is not matched by domestic employment will look for job offers in other countries (2) poverty has no effect on Indonesian labor migration, there are inhibiting factors such as high costs for prospective migrants through various procedures and moving costs reaching more than six times the salary that will be received (3) GRDP per capita has no effect on Indonesian labor migration, because the average income in an area which is seen as an indicator of population welfare does not reflect individual prospective migrants (4) Education has a negative effect on Indonesian labor migration , the higher the education will reduce the number of migration and the lower the level of education will increase the number of Indonesian labor migration.